2021
DOI: 10.1097/brs.0000000000004048
|View full text |Cite
|
Sign up to set email alerts
|

Complications and Revision Rates in Minimally Invasive Robotic-Guided Versus Fluoroscopic-Guided Spinal Fusions

Abstract: Study Design. Prospective, multicenter, partially randomized. Objective. Assess rates of complications, revision surgery, and radiation between Mazor robotic-guidance (RG) and fluoroguidance (FG). Summary of Background Data. Minimally invasive surgery MIS ReFRESH is the first study designed to compare RG and FG techniques in adult minimally invasive surgery (MIS) lumbar fusions. Methods. Primary endpoints were analyzed at 1 year follow-up. Analysis of variables through Cox logistic regression and a Kaplan-Meie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…In the prospective comparative MIS ReFRESH study, Good et al [ 1 ] showed that MIS robotic-guided surgery had 5.8 times fewer surgical complications related to screw placement and 11.0 times fewer revision surgeries compared to MIS fluoroscopic-guided surgery. The study also showed a reduction of intraoperative radiation exposure by 80% with robotic guidance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the prospective comparative MIS ReFRESH study, Good et al [ 1 ] showed that MIS robotic-guided surgery had 5.8 times fewer surgical complications related to screw placement and 11.0 times fewer revision surgeries compared to MIS fluoroscopic-guided surgery. The study also showed a reduction of intraoperative radiation exposure by 80% with robotic guidance.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature demonstrates that robotic-guided spine surgery leads to decreased implant-related complications, revision surgeries, and intraoperative radiation exposure while achieving a high a degree of implant accuracy [ 1 - 4 ]. Given the potential advantages to minimally invasive robotic-guided spine surgery combined with navigation and the latest robotic software advancements, utilization of these invaluable intraoperative tools is expected to increase.…”
Section: Introductionmentioning
confidence: 99%
“…The current literature indicates that the accuracy and precision with the use of robotics is highly effective, both in cadaver studies and patient cases. 29 The complication rate was reduced in two studies reviewing robot-assisted MISs in comparison with fluoroscopy-guided surgeries, 3 , 30 and there were few studies that indicated lower revision surgery and revision rates with the use of robotics. 3 , 31 , 32 Kantelhardt et al 3 reported a reduction in average length of hospital stay by 27%.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, few complications happened in the Tuoshou group, which is consistent with the high safety of robotic surgery. Additionally, similar to other spinal surgical robots, the Tuoshou robot only needs one time of three-dimensional scan during the operation, which greatly reduces radiation exposure [ 27 , 28 ].…”
Section: Discussionmentioning
confidence: 99%